Servant leadership theory in practice: North America's leading public libraries. (March 2020) - Lo, Patrick; Allard, Bradley; Wang, Na; Chiu, Dickson K.W.
This study aims to understand the current North American public library directors' views and perceptions of successful library leadership in the 21st century. It was carried out based around a series of semi-structured interviews with 10 top-level directors of public libraries in the United States and Canada, which were published in the book World's Leading National, Public, Monastery and Royal Library Directors: Leadership, Management: Future of Libraries . The data collection method for this study consisted of narrative analysis of the 10 interviews utilizing Robert Greenleaf's servant leadership theory, which highlights the leader's desire to serve others first and foremost. With the current trends of increased globalization, digitization, and cultural diversity, among others, public libraries need to have leadership focused on creating shared-power environments encouraging collaboration. Analysis of these interviews showed that many of the directors' responses were quite similar to the concepts discussed in servant leadership. The library directors, through their leadership philosophies, benefited in boosting team cohesion, fostering collaboration, increasing creativity, and promoting morality-centered self-reflection amongst leaders, thereby helping their libraries gain and maintain competitive advantage, and improving the overall ethical culture of their organizations. The results of this study would be of interest to library professionals interested in management as well as LIS students who want to understand how library directors view successful traits of library leadership.